1988
DOI: 10.1093/oxfordjournals.humrep.a136762
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization through spermatozoal microinjection: significance of acrosome reaction

Abstract: Acrosome-reacted spermatozoa were microinjected into the perivitelline space of mouse oocytes. After 2 h incubation in culture medium containing lactate and albumin, spermatozoa were transferred into culture medium containing 12 mM of dibutyryl cyclic guanosine 3',5'-monophosphate (dbcGMP) and 10 mM imidazole for 20 min. One motile spermatozoon was injected into the perivitelline space of each oocyte. Fertilization was recognized by the presence of a second polar body and two pronuclei. The overall fertilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…The percentage of acrosome free spermatozoa could be further increased when the incubation in T6 was followed by the incubation in medium containing the cation ionophore A23187 and1 or medium containing a mixture of dbcGMP and imidazole. Our data confirmed the findings of Lacham et al (1989) but are in disagreement with the results of Yamada et al (1988). In the latter study the higher percentage of acrosome free spermatozoa after treatment by dbcGMP and imidazole might be due to the fact that the triple stain technique was used for assessing the acrosomal status.…”
Section: Discussionsupporting
confidence: 69%
“…The percentage of acrosome free spermatozoa could be further increased when the incubation in T6 was followed by the incubation in medium containing the cation ionophore A23187 and1 or medium containing a mixture of dbcGMP and imidazole. Our data confirmed the findings of Lacham et al (1989) but are in disagreement with the results of Yamada et al (1988). In the latter study the higher percentage of acrosome free spermatozoa after treatment by dbcGMP and imidazole might be due to the fact that the triple stain technique was used for assessing the acrosomal status.…”
Section: Discussionsupporting
confidence: 69%
“…Our results are in contrast to those obtained by Yamada et al (1988) and Mann (1988). Yamada et al (1988) reported on diploid mouse embryos after sperm microinjections, but they gave no evidence that the sperm genome was included in the chromosomal complement of the embryo. However, Mann (1988) reported on newborn mice from microinjected oocytes.…”
Section: Discussioncontrasting
confidence: 99%
“…In nearly all experiments performed until now, the microinjection of sperm under the zona pellucida failed to result in fertilization (Westhusin, 1986;Barg et al, 1986;Green, 1987) or embryonic development (Metka et al, 1985;Laws-King et al, 1987;Lassalle et al, 1987;Yamada et al, 1988). Mostly, fertilization was proven by the presence of a second polar body and two pronuclei.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the sperm injection needle always passes through the ZP successfully, even when the operator is inexperienced. Yamada et al (1988) presented a procedure for the insertion of the sperm injection needle into the PVS of mouse oocytes with a series of photographs. According to their method, the path of the sperm injection needle through the ZP differs from that of the force used to hold the ovum.…”
Section: Procedures For Microinjection Of Sperm Intomentioning
confidence: 99%